Accumulation of storage iron in patients treated for iron-deficiency anaemia. Issue 5962 (12th April 1975) - Bentley, D P; Jacobs, A
Abstract : The repletion of iron stores after treatment was studied in 38 patients with uncomplicated iron-deficiency anaemia. The serum ferritin concentration rose significantly when oral treatment was continued for two months after the attainment of a normal haemoglobin concentration. Patients treated with a total-dose infusion of iron dextran had thehighest final serum levels, which were significantly greater than in patients given Ferro-Gradumet. Oral ferrous sulphate was almost as effective as parenteral iron in producing iron stores.